Blending and emission characteristics of biogasoline produced using CaO/SBA-15 catalyst by cracking used cooking oil. (1st January 2022) - Ge, Shengbo; Ganesan, Ramya; Sekar, Manigandan; Xia, Changlei; Shanmugam, Sabarathinam; Alsehli, Mishal; Brindhadevi, Kathirvel
Graphical abstract: Highlights: CaO/SBA-15 catalyst showed best catalytic activity in cracking used cooking oil in a fixed bed reactor. Used cooking oil was converted into 70% of liquid hydrocarbons with 69.7% gasoline selectivity. Bio Gasoline obtained from the liquid fuel exhibited comparable characteristics with commercial gasoline. 10% blend of Bio Gasoline showed best activity in terms of Torque and Brake thermal efficiency. Compared to gasoline. Low CO, NO and SO2 emissions project the harmless nature of the Bio Gasoline. Abstract: The aim of this work is to crack the used cooking oil in a fixed bed cracking unit using impregnated CaO/SBA-15 catalyst to yield liquid hydrocarbons with high % of biogasoline (BioG)fraction. Further, to investigate the capacity of the biogasoline fraction as well as the bio gasoline blends with fossil gasoline in increasing its efficiency. The porous morphology, pore distribution and surface area, elemental composition and phase formation of catalysts were analysed by Scanning electron Microscopy, Surface area analyser and X-ray diffraction techniques. All the synthesized materials were crystalline and least changes were observed with incorporation of CaO on SBA-15. The morphology of the materials were as expected without much agglomeration. SBA-15 exhibited fair surface area of around 1300 m 2 /g and discrete pores gas chromatography mass spectrometry (GC–MS). Among the catalysts, the composite material, CaO/SBA-15 (4 wt%) efficiently cracked 97% of used cooking oil into 70% liquid products and 69.7% of biogasoline which was confirmed using gas chromatography-mass spectrometry (GC–MS). BioG showed a good Calorific value of 10000 MJ/Kg which was comparable to that of petroleum fuel. Results of the engine test indicated that using biogasoline–gasoline blended fuels, torque output and fuel consumption of the engine increased when compared to gasoline; CO and SO2 emissions decreased largely due to the oxidation, CO2 emission increased because of the improved combustion and NOX emission from bio gasoline blends was low than gasoline.